Analysis of Technology Acceptance Model Method on Dana E-Wallet Users in Langsa City - Nurjanah, Nurjanah; Buchari (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
The research was conducted to know the effect of convenience, benefits, and trust on the use of Dana e-wallets in Langsa City. This study uses primary data sourced from research questionnaires with a sample of 75 respondents who are users of the Dana application. Methods of data analysis using multiple linear regression equation, t-test, F test, and test the coefficient of determination (R2). The results of the t-test show that ease has a significant effect on the use of Dana's e-wallet. Benefits have a significant effect on the use of Dana's e-wallet. Trust has a significant effect on Dana's e-wallet use. Then, the results of the F test, simultaneously convenience, benefits, and trust significantly affect the use of the Dana e-wallet. The results of the coefficient of determination (R2) obtained 57.2% convenience, benefits, and trustable to explain the dependent variable of the use of e-wallet Dana and 42.8% explained by other variables not included in this study.